Effects of nicotinamide mononucleotide on older patients with diabetes and impaired physical performance: A prospective, placebo‐controlled, double‐blind study. Issue 1 (28th November 2022) - Akasaka, Hiroshi; Nakagami, Hironori; Sugimoto, Ken; Yasunobe, Yukiko; Minami, Tomohiro; Fujimoto, Taku; Yamamoto, Koichi; Hara, Chikako; Shiraki, Akihiko; Nishida, Kohji; Asano, Kento; Kanou, Masanobu; et al.
Abstract : Objective: Nicotinamide adenine dinucleotide regulates various biological processes. Nicotinamide mononucleotide (NMN) increases its intracellular levels and counteracts age‐associated changes in animal models. We investigated the safety and efficacy of oral nicotinamide mononucleotide supplementation in older patients with diabetes and impaired physical performance. Method: We carried out a 24‐week placebo‐controlled, double‐blinded study of male patients with diabetes aged ≥65 years with reduced grip strength (<26 kg) or walking speed (<1.0 m/s). The primary end‐points were to determine the safety of NMN oral administration (250 mg/day), and changes in grip strength and walking speed. The secondary end‐points were to determine the changes in various exploratory indicators. Results: We studied 14 participants aged 81.1 ± 6.4 years. NMN was tolerable without any severe adverse events. The changes in grip strength and walking speed showed no difference between the two groups: 1.25 kg (95% confidence interval −2.31 to 4.81) and 0.033 m/s (−0.021 to 0.087) in the NMN group, and −0.44 kg (−4.15 to 3.26) and 0.014 m/s (−0.16 to −0.13) in the placebo group, respectively. There were no significant differences in any exploratory indicators between the two groups. However, improved prevalence of frailty in the NMN group ( P = 0.066) and different changes in central retinal thickness between the two groups ( P = 0.051) was observed. Conclusion: In older male patients with diabetes and impaired physical performance, NMN supplementation for 24 weeks was safe, but did not improve grip strength and walking speed. Geriatr Gerontol Int 2023; 23: 38–43 . Abstract : Oral administration of nicotinamide mononucleotide (250 mg/day) Twenty‐four‐week placebo‐controlled, double‐blind study Fourteen male patients with diabetes aged ≥65 years Grip strength (<26 kg) or walking speed (<1.0 m/s) The primary endpoint The safety of nicotinamide mononucleotide administration The changes in grip strength and walking speed The secondary endpoints include Japanese version of the Cardiovascular Health Study frailty components Muscle volume or glucose metabolism Central retinal thickness or retinal vascular density Nicotinamide mononucleotide supplementation for 24 weeks was safe, but did not improve grip strength and walking speed.